Neurological adverse events associated with PD-1/PD-L1 immune checkpoint inhibitors - Zhou, Yanting; Li, Hongyan (Frontiers in Neuroscience, 2023)
Immunotherapy is a promising method for cancer treatment. Among them, immune checkpoint inhibitors targeting PD-1/PD-L1 are increasingly used for certain cancers.However, with the widespread use of such drugs, reports of immune-related adverse events (irAEs) are also increasing. Neurological adverse events (nAEs) are one of the irAEs that affect the peripheral and central nervous systems. They are characterized by low incidence, hard to diagnose, and life-threatening risks, which have a significant impact on the prognosis of patients. Biomarker-based early diagnosis and subsequent treatment strategies are worthy of attention, and comprehensive management of irAEs is important for optimizing patients' quality of life and long-term outcomes. In this review, we summarized the mechanisms, common symptoms, early biomarkers, treatments, and future research directions of nAEs, in order to provide a comprehensive overview of immune checkpoint inhibitor-related nAEs targeting PD-1/PD-L1.